Olive (Olea Europaea L.) Leaf Extract Boosts Antioxidant Status And Attenuates Hepatic And Pancreatic Changes In Diabetic Rats (Applied Biological Research, 2019)
The purpose of this study was to evaluate the antioxidant, oxidative DNA  damage and hepatoprotective effects of olive (Olea europaea L.) leaf extract  (OLE) on experimental diabetic rats. These effects of OLE were studied  using streptozocin-induced diabetic rats. Antioxidant enzyme activities,  oxidative DNA damage analysis and protein oxidation were evaluated  spectrophotometrically methods. In addition, histological examination of the liver and pancreas was performed routinely with paraffin embedding  and staining method. Protein carbonyl level and 8-hydroxy-2' – deoxyguanosine (8-OHdG) concentration decreased in OLE administrated  group compared to diabetic group. Further, OLE treatment significantly increased superoxide dismutase and glutathione peroxidase activities. It was  observed that OLE remarkably attenuated degenerative and necrotic  changes in liver and pancreatic tissues. Consequently, it appears that OLE  strengthens the antioxidant defense system, protects against oxidative DNA  damage, and has a hepatoprotective effect on diabetic rats.
Keywords: Antioxidant; diabetics; 8-OHdG; hepatoprotective; olive